Biodesulfurization of the mixture of dibenzothiophene and its alkylated derivatives by Sphingomonas subarctica T7b - Ida Bagus Wayan Gunam; Teruo Sone; Kozo Asano (Indonesian Journal of Biotechnology, 2021)
Organosulfur compounds classified as dibenzothiophenes (DBTs) and their derivatives are contained in petroleum. When used as fuel, these substances release SOx emissions, thus contributing to air pollution, acid rain, and climate change. Therefore, it is necessary to reduce the content of these organic sulfur compounds in fuels and one way to achieve this is through bacterial desulfurization. This study reports the biodesulfurization process of a mixture of DBT, 4-hexyl DBT, 4,6-dibutyl DBT, and various organosulfur compounds in light gas oil (LGO). The experiment was conducted by treating 1 mL of aromatic organosulfur compounds with 100 mg/L in n-tetradecane or 1 mL LGO with 5 mL mineral salts in sulfur-free medium, incubated at 27 °C for 5 days with shaking at 273 rpm. Gas chromatography analyses revealed that the growing Sphingomonas subarctica T7b cells desulfurized and converted 88.29% of DBT to 2-hydroxybiphenyl as a metabolite while a mixture of DBT and 4,6-dibutyl DBT was desulfurized at 86.40% and 7.00%, respectively. Furthermore, the mixture of DBT, 4-hexyl DBT, and 4,6-dibutyl DBT had a desulfurization percentage of 84.40%, 41.00%, and 6.66%, respectively, after five days of incubation. The compounds were observed to desulfurize slightly better as single compounds compared to when mixed with other aromatic sulfur compounds.